2008
DOI: 10.1002/ddrr.12
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of swallowing and dysphagia

Abstract: The neurobiological study of swallowing and its dysfunction, defined as dysphagia, has evolved over two centuries beginning with electrical stimulation applied directly to the central nervous system, and then followed by systematic investigations that have used lesioning, transmagnetic stimulation, magnetoencephalography, and functional magnetic resonance imaging. The field has evolved from mapping the central neural pathway and peripheral nerves, to defining the importance of specific regions of the lower bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 159 publications
(155 reference statements)
1
111
0
5
Order By: Relevance
“…As goal-directed activity is reflected in cognitive control exerted by the prefrontal cortex (25,26), we performed fMRI during the period immediately prior to swallowing (hereafter the "preswallow period") to test the hypothesis that activity in the prefrontal cortex increases following satiation and is correlated with the effort required to swallow. This would provide corroborating evidence for swallowing inhibition as well as providing additional insight into the cortical brain processes involved in the regulation of swallowing (27)(28)(29)(30)(31).…”
Section: Significancementioning
confidence: 53%
See 1 more Smart Citation
“…As goal-directed activity is reflected in cognitive control exerted by the prefrontal cortex (25,26), we performed fMRI during the period immediately prior to swallowing (hereafter the "preswallow period") to test the hypothesis that activity in the prefrontal cortex increases following satiation and is correlated with the effort required to swallow. This would provide corroborating evidence for swallowing inhibition as well as providing additional insight into the cortical brain processes involved in the regulation of swallowing (27)(28)(29)(30)(31).…”
Section: Significancementioning
confidence: 53%
“…Previous studies of swallowing (27)(28)(29)31), including our earlier study (17), have identified the lateral precentral gyrus, lateral postcentral gyrus, insula, operculum, cingulate cortex, and superior temporal gyrus as regions involved in the cortical regulation of swallowing. A crucial difference between those studies and the present study, however, is that brain images for the present study were acquired while liquid was held in the mouth rather than while it was being swallowed.…”
Section: Discussionmentioning
confidence: 72%
“…The oral phase of swallowing is initiated voluntarily while the pharyngeal and oesophageal phases occur via intraphase reflexes (Lang, 2009). Control of the phases represent a coordination among the brain stem and central cortical pathways (Miller, 2008).…”
Section: Normal Swallowingmentioning
confidence: 99%
“…Swallowing has been shown using fMRI studies to involve the precentral and postcentral gyri, the anterior cingulated gyrus and the insula (Miller, 2008). By using Transcranial Magnetic Stimulation, Hamdy and his colleagues showed that swallowing is bilaterally but asymmetrically represented in the cortical hemispheres, and that this representation is unrelated to handedness.…”
Section: Cortical Lesionsmentioning
confidence: 99%
See 1 more Smart Citation